Investigations on incidence and histopathology of toxoplasmosis in domestic mammals (dogs and rabbits) in Brazil - Santos, Jefferson Andrade dos; Novloski, G.; Pereira, E. F. da Costa; Rezende, A. M. Langenegger de (Pesquisa Agropecuaria Brasileira, 2014)
Toxoplasmosis - caused by the parasite Toxoplasma gondii - has been diagnosed in Brazil following post-mortem examination of thoracic and abdominal organs in dogs and rabbits but not in cattle, swine, sheep, goats, horses, asses, mules, cats, guinea-pigs, rats and mice. During the period 1933 lo 1966 out of a total of 873 dogs autopsied 16 (1.8%) had the infection and of 499 rabbits examned 6 (1.2%) were infected. Of the organs examined lesions were most commonly found in the liver, spleen and lungs. The histopathologic lesions consisted of necrosis, which had a filamentous aspect and very acidophilic necrotic material; practically there was little inflammatory reaction around the necrotic lesions. In two rabbits the disease caused extensive necrosis of the mesenteric lymph nodes and the same type of lesions in the spleen. Apparently the toxoplasmosis was always the cause of the death of the animals with the infection, with exception of one rabbit which died due to an malignant uterine neoplasm.